(untitled) (Journal of history, 2023)
The purpose of this article is to reveal the features of the system formation of Kazakh officials on the territory of the Inner Horde by analyzing the post of deputy created by the imperial authorities along the border lines. In historical science, the presented topic has not been studied, and this article for the first time reveals the incorporation mechanism of Kazakh population representatives on the position of the Inner Horde deputy, a new range of their duties and a different aspects of their interaction with representatives of the regional administration (border line commanders, officials of the Orenburg, then Astrakhan provincial government), sultans, rulers and residents, namely the Cossacks, Yurt, Kundra Tatars, Bashkirs and Russians and other peoples who lived on the transboundary zone. The social background and educational level of the appointed deputies varied. The materials of the article are based on archival documents extracted from the funds of the Central State Archive of the Republic of Kazakhstan, revealing the areas of activity of Kazakh deputies on the border line, often complex and multifaceted. The main methodological framework of the article is the fact that the Kazakh deputies of the border lines were active participants in the historical events that took place on the territory of the Inner Horde. Key words: Inner horde, frontier line, service of deputies, Kazakh officials, Russian Empire